A rare case of iatrogenic tension pneumocephalus - Agu OD; Njeze NR; Uduma FU; Obikili EN; Eze KC (Ibom Medical Journal, 2019)
Background: Pneumocephalus is a common complication of craniotomies. Since it has little or no clinical significance, it usually requires no treatment. However, tension pneumocephalus could also be associated with raised intracranial pressure and neurological deterioration. This emergency requires immediate radical approach to achieve surgical decompression. Objectives: To create awareness that the onset of post craniotomy tension pneumocephalus may be delayed and also to show that the radiological appearance may deviate from the classical Mount Fuji model. Case Description: A pituitary mass was successfully removed overseas from a 49-year-old man by transcranial approach. He improved, returned home and presented himself for clinical review on arrival without any significant complaint. The patient was brought back in coma two weeks later with blood pressure of 150/100 mmHg and aseptic CSF rhinorrhoea. The cranial CT scan showed marked dilatation of the lateral ventricles with obvious gas lucencies (Hounsfield unit = -1000HU). Concluson: High index of suspicion of tension pneumocephalus should be borne in mind in post operative reviews of craniotomy patients, as timely appropriate intervention is imperative.